Pelatihan Pengendalian Penyakit Busuk Batang Vanili (BBV) Di Desa Srimenganten, Kecamatan Pulau Panggung, Kabupaten Tanggamus, Provinsi Lampung - Endang Nurcahyani; Hardoko Insan Qudus; Sumardi; Rina Maryani; Yulianty; Bambang Irawan; Salman Farisi (AMMA : Jurnal Pengabdian Masyarakat, 2025)
Srimenganten Village, located in Pulau Panggung Sub-district, Tanggamus Regency, Lampung Province, is an agrarian area with vanilla as one of its main commodities. However, vanilla productivity in this village has declined due to the outbreak of Vanilla Stem Rot Disease (BBV), caused by the fungus Fusarium oxysporum f.sp. vanillae. To address this issue, a community service program was conducted through training on BBV disease management for vanilla farmers in Srimenganten Village. The training covered topics such as disease symptom identification, prevention methods, and environmentally friendly control techniques. The effectiveness of the training was evaluated by comparing participants' pre-test and post-test results. The evaluation showed an average increase in participants' knowledge scores by 33.3 points, with a percentage increase of 61.3%. This indicates that the training effectively enhanced farmers' understanding of BBV disease management. It is expected that this increased knowledge will be applied in vanilla cultivation practices, thereby improving productivity and the quality of harvests.